The nutritional profile comparison between the white and purple Açaí in the mesoregions of Pará, Brazil - Coutinho, Rosemary Maria Pimentel; Rocha, Juliana De Cássia Gomes; Neves, Nathália; Silva, Vera Lúcia Dias da; Seixas, Vitória Nazaré Costa; Hermosín-Gutiérrez, Isidro; Carvalho, Antonio Fernandes de; Stringheta, Paulo Cesar (Frontiers in Nutrition, 2024)
The study targeted to compare the nutritional profile of two varieties of açaí, the white and purple, found in different mesoregions of Pará, Brazil. The research focused on analyzing levels of total phenolics, total anthocyanins, antioxidant capacity, and mineral composition in these two varieties. The study sought to identify significant differences between the two varieties in terms of nutritional composition and antioxidant potential, providing valuable information into the specific nutritional and functional properties of each type of açaí studied. Higher levels of total phenolics, total anthocyanins, and antioxidant capacity were observed in purple açaí fruits, with values of 806.17 ± 17.48 mgGAE/100 g, 81.73 ± 1.77 mg/100 g, and 19.25 ± 0.35 μmol of Trolox equivalent (TE)/g, respectively, compared to 401.92 ± 52.70 mgGAE/100 g, 37.70 ± 5.34 mg/100 g, and 6.17 ± 1.07 μmol TE/g in white açaí. HPLC-MS analysis identified and quantified monomeric anthocyanins in white açaí, using two distinct analytical methods, revealing average values of 0.29 and 1.05 μg/100 g for cyanidin-3-glucoside and between 0.74 and 3.13 μg/100 g for cyanidin-3-rutinoside, respectively, which were higher than those found in yellow tropical fruits. The quality of both purple and white açaí varied significantly among mesoregions, with fruits from floodplain soils demonstrating superior quality compared to those from sandy and solid soils in southeastern Pará. Mineral composition and microbiological characteristics were similar between white and purple açaí. These findings underscore the significant influence of mesoregion and soil type on açaí quality, emphasizing the superiority of fruits grown in floodplain soils.